Profile of Critical Thinking of Grade XI Students at SMAN 1 Torue in Solving Circle Problems Based on Van Hiele's Levels of Thinking - Cheysa Putri Pratama; Sukayasa Sukayasa; Ibnu Hadjar; Nurhayadi Nurhayadi (Journal of Educational Sciences, 2026)
Critical thinking is an essential competence in mathematics learning, particularly in circle topics that demand conceptual understanding and geometric reasoning. One relevant framework for examining this ability is Van Hiele’s levels of geometric thinking. This study aims to describe students’ critical thinking skills in solving circle problems based on their Van Hiele levels. A qualitative descriptive approach was employed. The subjects consisted of three Grade XI students, each representing Van Hiele level 0 (visualization), level 1 (analysis), and level 2 (informal deduction). Data were collected through circle problem-solving tests and interviews. Critical thinking was analyzed using Ennis’s indicators: elementary clarification, advanced clarification, strategies and tactics, and inference. The findings show that students at the visualization level understood problems and applied basic procedures but did not demonstrate sufficient inference and evaluation skills. Students at the analysis level explained relationships among circle elements and applied strategies appropriately, though their ability to recheck results was limited. Meanwhile, students at the informal deduction level exhibited more comprehensive critical thinking across all indicators. The study concludes that the higher the Van Hiele level, the stronger the quality of students’ critical thinking in solving circle problems.